Modelagem computacional de ventosas de duplo efeito como mecanismo de alívio do golpe de aríete - Peroba Júnior, Fernando (2007)
This work presents a computer simulation of the air valves of double effect in Hydraulics Transients in pipelines through the use of the computer code UFC6 developed in the Hydraulic Computational Laboratory (HCL) of the Universidade Federal do Ceará. Air valves are devices designed to relief the effects of the water hammer phenomena throughout expelling air entrapped in the conduit. The boundary conditions applied for air valves is very complex and results in a non-linear equation. In order to solve this non linearity, it was used the parabolic approximation method in the intervals when air flows in subsonic regime. This method not only is easy to be implemented but also requires little computational effort. Though widely used, the subject of air valves and water hammer has few works published worldwide.